The effect of training on the activity of creatine kinase (CK) and lactate dehydrogenase (LD) and uric acid concentration in plasma of elite boxers - Hübner-Wozniak, E.; Lutoslawska, G.; Kusior, A.; Gajewski, J. (Human Movement, 2004)
Purpose The aim of the present study was to examine the rate of changes in the activity of creatine kinase and lactate dehydrogenase and uric acid concentration in plasma during boxing training.